166Dy/166Ho-labeled porous hydroxyapatite microparticles for treatment of inflammatory joint diseases – Exploring the advantages of in vivo generator - Sourav Patra; Khajan Singh; Avik Chakraborty; Shahiralam Khan Mohammed; Sutapa Rakshit; Rubel Chakravarty; Sudipta Chakraborty (Scientific Reports)
Abstract Holmium-166 [T½ = 26.8 h, Eβ − (max) = 1.74 MeV (48.7%) and 1.85 MeV (50.0%); Eγ = 80.6 keV (10.6%)] is one of the most promising radionuclides in radiation synovectomy (RSV) for the treatment of inflammatory joint diseases, especially of large joints. However, short half-life of 166Ho is a practical impediment toward its extensive utility. This study aims to address this limitation by developing a potent formulation where 166Ho in transient radioactive equilibrium with 166Dy [T½ = 81.5 h] is used as its in vivo generator. In this regard, a chelator-free radiolabeling approach was optimized using porous hydroxyapatite (HA) microsphere (2–10 μm) as a carrier platform of 166Dy/166Ho. Sorption of 166Dy/166Ho in porous HA followed Langmuir-Freundlich isotherm and pseudo-second order kinetics, indicating chemisorption of the radiolabeling process. The formulation retained its radiochemical integrity in PBS and human serum upto a period of 14 d. The preclinical study showed near-exclusive retention of the radiolabeled microparticles within the injected joint cavity of healthy Wistar rats with no translocation of 166Dy and 166Ho. Overall, the reported studies indicated the potency developed 166Dy/166Ho-labeled porous HA microsphere for the treatment of inflammatory joint diseases and an in vivo generator of 166Ho.